Kreativitas Guru PAI Dalam Mengembangkan Bahan Ajar Di Madrasah Darut Taqwa 1 Watukosek Gempol Pasuruan - Anasro, Anasro; Insyirah, Ilusia; El-Yunusi, Muhammad Yusron Maulana (Impressive: Journal of Education, 2023)
During the teaching and learning process, the creativity of a teacher is very important to achieve maximum learning and the expected educational goals. The purpose of this research is to study the development of teaching materials developed by teachers at Madrasah Aliyah Darut Taqwa 1 Watukosek Pasuruan to achieve optimal educational and learning goals. this research uses a qualitative approach. Data collection techniques are done through interviews, observations, and documentation studies. Data analysis procedures are data reduction, data display, and verification. The results showed that teachers in the process of developing teaching materials have a variety of creativity, such as making their own, borrowing from the school library, buying from shops, and downloading from the website. Various types of teaching materials are used in the learning process, such as handouts, textbooks, modules and LKS. Teachers make efforts in developing teaching materials by designing and creating teaching materials needed according to the materials and sub-materials in teaching Islam by using the ASSURE learning design model.